2D Materials: Metallic MXene Saturable Absorber for Femtosecond Mode‐Locked Lasers (Adv. Mater. 40/2017). Issue 40 (20th October 2017) - Jhon, Young In; Koo, Joonhoi; Anasori, Babak; Seo, Minah; Lee, Ju Han; Gogotsi, Yury; Jhon, Young Min
Abstract : In article number1702496, Ju Han Lee, Yury Gogotsi, Young Min Jhon, and co‐workers demonstrate that 2D transition‐metal carbides, nitrides, and carbonitides, called MXenes, can be excellent saturable absorbers to generate femtosecond mode‐locked pulsed lasers in a fiber laser cavity. The promise of MXenes in broadband laser applications is suggested due to the wide range of superb optical absorptions, from the visible to the terahertz range, which results from the unique metallic characteristics.